Drug Abuse as an Extra-Ordinary Crime: Some Legal and Political Debates - Aryanto, Putra Nova (Dinasti Publisher, 2025)
As though a double-edged knife, on the one hand, Narcotics can be a panacea for various critical illnesses, but on the other hand, Narcotics can destroy all joints and organs of the human body. Both sides are very much determined by who the narcotics are used for. As one type of Narcotics, Drugs are the type most abused. However, the problems arising from drugs are in fact not only about abuse. Drug abuse is then used as a momentum to form an organized business sector with a structured and systematic sales mechanism. Of course, this is what makes drug abuse categorized as an extraordinary crime that requires extraordinary handling as well. This research will reveal various types of drug abuse as well as national and international efforts and efforts in fighting drug crimes. This research uses qualitative research methods with a literature approach. The data obtained comes from several regulations, such as Law Number 35 of 2009 concerning Narcotics and several other regulations and policies, as well as international cooperation carried out by Indonesia. The results of the study state that Indonesia is currently in a state of drug emergency, so it is necessary to strengthen and innovate government policies to tackle drug crimes that have been committed at this time, as a form of government commitment to eradicating drugs from the base to the upstream of the problem.